2006
DOI: 10.1079/ijt2006101
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal population trends of Megalurothrips sjostedti and Frankliniella occidentalis (Thysanoptera: Thripidae) and their natural enemies on French bean Phaseolus vulgaris (Fabaceae)

Abstract: A field experiment was conducted to track the daily population trends and occurrence of the flower thrips Megalurothrips sjostedti Trybom and Frankliniella occidentalis (Pergande), and their indigenous natural enemies Orius spp. and Ceranisus menes (Walker), infesting French beans. French beans in monocrop or interplanted with six companion crops (Zea mays L., Coriandrum sativum L., Tagetes erecta L., Brassica oleracea var. acephala L., Daucus carota L. and Capsicum annuum L.), and two chemical insecticides, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…Our results also support those of Kareiva (1982) working on the dispersal pattern of two crucifer-feeding flea beetles, Phyllotreta cruciferae and Phyllotreta striolata under field conditions and Rhainds and Shipp (2004) working on the dispersal pattern of adult F. occidentalis in greenhouse crops, who reported that over time insect dispersal can happen over a relatively wide spatial scale with each adjacent Dispersal of adult F. occidentalis was at the peak at 10:15 h and 13:15 h in the first and second planting seasons, respectively. Our results corroborate those of Kasina et al (2006), who reported that dispersal of adult F. occidentalis on field-grown French bean was at peak at 10:00-13:00 h. Dispersal of adult F. occidentalis was dependent on temperature with minimal dispersal activity at temperatures below 15°C and maximum activity at 19°C. However, at temperatures of 21-24°C, there was a decline in dispersal activity of adult F. occidentalis in the first planting season.…”
Section: Discussionsupporting
confidence: 91%
“…Our results also support those of Kareiva (1982) working on the dispersal pattern of two crucifer-feeding flea beetles, Phyllotreta cruciferae and Phyllotreta striolata under field conditions and Rhainds and Shipp (2004) working on the dispersal pattern of adult F. occidentalis in greenhouse crops, who reported that over time insect dispersal can happen over a relatively wide spatial scale with each adjacent Dispersal of adult F. occidentalis was at the peak at 10:15 h and 13:15 h in the first and second planting seasons, respectively. Our results corroborate those of Kasina et al (2006), who reported that dispersal of adult F. occidentalis on field-grown French bean was at peak at 10:00-13:00 h. Dispersal of adult F. occidentalis was dependent on temperature with minimal dispersal activity at temperatures below 15°C and maximum activity at 19°C. However, at temperatures of 21-24°C, there was a decline in dispersal activity of adult F. occidentalis in the first planting season.…”
Section: Discussionsupporting
confidence: 91%
“…Kasina et al (2006) observed peak population activity of Frankliniella occidentalis at 1300 hours in French bean Þelds. On the contrary, Ugine et al (2006) did not observe any effect of daytime on the population activity of F. occidentalis on impatiens ßowers.…”
Section: Discussionmentioning
confidence: 80%
“…Besides temperature, Lewis (1973) discovered that light intensity was an equally important factor affecting the ßight of thrips. However, according to Ugine et al (2006), sampling time during the day has no effect on F. occidentalis density across impatiens ßower bud stages, but Kasina et al (2006) demonstrated that the average population peak of F. occi- In this study, different time of daily activities were observed in thrips population on mango ßow-ers collected by different sampling techniques with the highest efÞciency demonstrated by the CO 2 immobilization technique. In the washing, shaking, and CO 2 immobilization techniques, thrips populations peaked during midday.…”
Section: Efficiency and Precision Of Sampling Methodsmentioning
confidence: 60%